2000
DOI: 10.1017/s0950268800004805
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of case fatality rates of meningococcal disease during outbreaks in Makkah, Saudi Arabia, 1987–97

Abstract: We studied case-fatality rates (CFRs) among cases of meningococcal disease (MCD) admitted to Makkah (Saudi Arabia) hospitals during the period 1988-97. Of 483 cases, 431 (89.2%) were due to strains of serogroup A, 31 (6.4%) to serogroup W135, 16 (3.3%) to serogroup C, and 5 (10%) to serogroup B. Eighty-one patients died (case fatality rate (CFR)) 16.8%, 95% CI 13.5%, 20.4%). The CFR in infections due to serogroup A strains was 14.8%, and for other serogroups it was 32.7% (95% CI 20.3%, 47.1%). The CFR of MCD d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…26 In 1997 during the month of Ramadan in the Umrah season, an increase in the number of cases of serogroup A disease was noted with over 70% of the cases being religious visitors. 27,28 In response, ciprofloxacin chemoprophylaxis was given to all household contacts of a confirmed or suspected case and a vaccination programme with the bivalent A/C vaccine was initiated. In addition the monovalent A vaccine was temporarily incorporated into the routine Saudi childhood vaccination programme for children aged 3 months to 2 years.…”
Section: Past Strategiesmentioning
confidence: 99%
“…26 In 1997 during the month of Ramadan in the Umrah season, an increase in the number of cases of serogroup A disease was noted with over 70% of the cases being religious visitors. 27,28 In response, ciprofloxacin chemoprophylaxis was given to all household contacts of a confirmed or suspected case and a vaccination programme with the bivalent A/C vaccine was initiated. In addition the monovalent A vaccine was temporarily incorporated into the routine Saudi childhood vaccination programme for children aged 3 months to 2 years.…”
Section: Past Strategiesmentioning
confidence: 99%
“…Education campaigns were introduced and made for successful control of serogroup A meningococcal disease. Review of all cases of meningococcal disease at the hospitals in Mecca during the period 1988-97 revealed that 431 (89.2%) of 483 cases were due to strains of serogroup A, 31 (6.4%) to serogroup W135, 16 (3.3%) to serogroup C, and 5 (1%) to serogroup B [35]. In February 1999, because there was no evidence of ongoing epidemic meningococcal disease in the Kingdom of Saudi Arabia, the US Centers for Disease Control and Prevention (CDC) changed its recommendation and lifted the vaccination requirements for people traveling to Saudi Arabia [36].…”
Section: Risk For Travelersmentioning
confidence: 99%
“…Despite all the advances in the therapy, the CFR still remains unacceptably high (5%-10%). Recently published data on the CFR of meningococcal disease during outbreaks in Mecca in 1987-97 shows a higher rate, 16.7% [35]. Chemoprophylaxis may prevent secondary cases (among contacts of cases), but they comprise only 1%-2% of all meningococcal disease; hence, chemoprophylaxis is not considered an ideal method to control endemic and epidemic meningococcal disease.…”
Section: Preventionmentioning
confidence: 99%
“…5 Hajj and Umrah have been associated with a number of local and international meningococcal disease outbreaks, including a large serogroup A outbreak in 1987 and major serogroup W135 outbreaks in 2000 and 2001. [6][7][8][9] Returning international pilgrims carrying N. meningitidis were the vehicle for the exportation of the disease outside KSA and also the introduction of new serogroups into other regions of the world, affecting the global epidemiology of the disease. 3,10,11 A review of the literature on N. meningitidis carriage among Hajj and Umrah pilgrims and their household contacts was performed.…”
Section: Introductionmentioning
confidence: 99%